2008
DOI: 10.1016/j.adolescence.2007.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the Kenyan Kikuyu male circumcision ritual to future generations living in the United States

Abstract: This phenomenological research report from analysis of interviews with 18 participants focuses on the theme of transferring an age‐old initiation‐into‐manhood circumcision ritual to future generations of Kenyan Kikuyu who are living in the US. We identified three subthemes and found a strong indication that, while personally meaningful to the participants, the ritual, its meaning, and its impact likely will dwindle and possibly eventually be eradicated among future Kikuyu generations in America unless there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
(8 reference statements)
0
6
1
Order By: Relevance
“…As recent studies have found a link between circumcision and HIV infection, our research has uncovered a major challenge in reconciling public health prevention recommendations with indigenous cultural practices. During the rite of passage, these young men are taught about various responsible behaviors that would benefit them, their families, community, and the nation (Mbito & Malia, 2008;Munthali & Zulu, 2007;Niang & Boiro, 2007). Our study, however, found that 79.8% of participants reported that they were already sexually active before undergoing the traditional process of initiation and circumcision.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…As recent studies have found a link between circumcision and HIV infection, our research has uncovered a major challenge in reconciling public health prevention recommendations with indigenous cultural practices. During the rite of passage, these young men are taught about various responsible behaviors that would benefit them, their families, community, and the nation (Mbito & Malia, 2008;Munthali & Zulu, 2007;Niang & Boiro, 2007). Our study, however, found that 79.8% of participants reported that they were already sexually active before undergoing the traditional process of initiation and circumcision.…”
Section: Discussioncontrasting
confidence: 55%
“…Male circumcision is associated with various cultural factors, including religious sacrifice, rites of passage into adulthood, responsible manhood, and the promotion of hygiene (Auvert, Taljaard, Lagarde, Sobngwi-Tambekou, Sitta, & Puren, 2005;personal communication with ECHOTL chairperson Nkosi Matanzima, 2006). Newly circumcised men are prepared for new roles as adults and are taught the essential duties to their families and community members through a process called male initiation (le Roux, Niehaus, Koen, Seller, Lochner, & Emsley, 2007;Mbito & Malia, 2008). Anthropologists working in African societies have presented male initiation as secretive, culturally-tight rites of passage from boyhood to manhood (Boyle, Goldman, Svoboda, & Fernandez, 2002;Meissner & Buso, 2007;Munthali & Zulu, 2007;Niang & Boiro, 2007;Vincent, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these attributes, the 'ideal Ulwaluko man' is expected to be responsible, selfless, and respectful to family, elders, and society at large. A number of studies report similar findings that the ritual has the potential to develop character and responsible behaviour that would benefit initiates, their families, community, and the nation at large (Mavundla et al, 2009(Mavundla et al, , 2010Mbito & Malia, 2008;Niang & Boiro, 2007;Ntombana, 2009Ntombana, , 2011Wood & Jewkes, 1998).…”
Section: Ideal Ulwaluko Manmentioning
confidence: 89%
“…Before the coming of the missionaries and colonization, ethnic communities had some form of gender-based traditional sex education for the youth. For example, during the Kikuyu ethnic community circumcision, the young initiates were secluded from the community by gender to receive instructions on adulthood expectations (Mbito and Malia 2009). This included sexually responsible behavior.…”
Section: Sexualitymentioning
confidence: 99%